2021
DOI: 10.24191/jeeir.v9i2.13617
|View full text |Cite
|
Sign up to set email alerts
|

Mobile payment and e-wallet adoption in emerging economies: A systematic literature review

Abstract: Against the backdrop of greater smartphone and internet penetration across the emerging markets, electronic wallet (e-wallet) has emerged as a reliable and well-known digital payment method. The main purpose of this paper is to review the growing volume of studies on e-wallet adoption in this region. E-wallet is widely used worldwide, but it has yet to become mainstream in developing countries, including Malaysia. Hence, scholars have conducted numerous studies on e-wallet use, but there seems to be a lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…For the purpose of this study, we focus specifically on eWallet as an encompassing technological concept that facilitates mobile payments, using an eWallet system, and aim to understand the influence of specific antecedents on the intention to use eWallets, from the (existing or potential) customer's point of view. This definition is in line with Ramli and Hamzah (2021); the authors define eWallet as “ …. a mobile device-based platform that facilitates cashless payments of a sales transaction –either in proximity or remotely, between consumers and merchants or service providers .”…”
Section: Literature Reviewmentioning
confidence: 82%
See 1 more Smart Citation
“…For the purpose of this study, we focus specifically on eWallet as an encompassing technological concept that facilitates mobile payments, using an eWallet system, and aim to understand the influence of specific antecedents on the intention to use eWallets, from the (existing or potential) customer's point of view. This definition is in line with Ramli and Hamzah (2021); the authors define eWallet as “ …. a mobile device-based platform that facilitates cashless payments of a sales transaction –either in proximity or remotely, between consumers and merchants or service providers .”…”
Section: Literature Reviewmentioning
confidence: 82%
“…The terms “digital wallets” or “mobile wallets” have also been used interchangeably in lieu of “eWallets” in literature (cf. Mew and Millan, 2021; Ramli and Hamzah, 2021; Teng and Khong, 2021; Tun, 2020; U.S. Payments Forum, 2018; Yang et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the UTAUT model has been widely applied and tested for a variety of themes (Teng and Khong, 2021), such as m-wallet (Chawla and Joshi, 2019), E-wallet (Moorthy et al, 2021) and m-payment (Esawe, 2022a;Ramli and Hamzah, 2021), many scholars have recommended adding external factors to sequel the original UTAUT model. Furthermore, Flavian et al (2020) explained that literature in the vein of adoption and continued use of technology do not accurately capture the more rational factors of adoption, mainly because the consumer does not always make this decision relying on grounded and well-founded beliefs.…”
Section: Sjmementioning
confidence: 99%
“…Khiong et al (2022) concluded the perceived convenience has effect on the attitude in e-wallet usage. There are several studies show positive effect of convenience towards technology use (Lee et al, 2022;Ramli & Hamzah, 2021). However, there is also inconsistent finding where Satyagraha (2021) found no significant effect of convenience-use of Millennials' intention to use e-wallets.…”
Section: Conveniencementioning
confidence: 99%